A Descriptive Language of Dominion? Curial Inventories, Clothing, and Papal Monarchy c. 1300. (3rd July 2017) - Miller, Maureen C.
Abstract : Using evidence from both papal and cardinal inventories, as well as from cardinal wills, this essay argues that the papal curia developed a distinctive language for describing liturgical vestments in the late thirteenth and early fourteenth centuries that emphasised the peoples and places that made the materials and ornaments of these garments. Examples from inventories of local dioceses and religious houses are offered to illustrate the peculiarity of the curial descriptions, and comparisons are also made to royal and mercantile inventories. While the curial emphasis on the places and peoples producing the materials used in ecclesiastical vestments may simply have been the performance of connoisseurship within an elite institutional culture, the author suggests that it may also express the expansive papal claims to dominion articulated by Boniface VIII (1294–1303) and his immediate successors.